Air stable and efficient rare earth Eu(ii) hydro-tris(pyrazolyl)borate complexes with tunable emission colors. Issue 23 (25th October 2020) - Qi, Hao; Zhao, Zifeng; Zhan, Ge; Sun, Boxun; Yan, Wenchao; Wang, Chengbo; Wang, Liding; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract : Eu(ii ) complexes with high air stability and tunable emission colors were synthesized and characterized. Abstract : Luminescent rare earth Eu(ii ) complexes with a characteristic 5d–4f transition have shown potential in various applications. However, the exploration and further application of typical Eu(ii ) complexes are strongly impeded by their instability arising from the easily oxidation of Eu 2+ ions. In this work, three new Eu(ii ) complexes bis(hydro-tris(3-phenyl-5-methylpyrazolyl)borate)europium(ii ) (Eu(Tp Ph, Me )2 ), bis(hydro-tris(3-phenylpyrazolyl)borate)europium(ii ) (Eu(Tp Ph )2 ), and bis(hydro-tris(3, 5-diphenylpyrazolyl)borate)europium(ii ) (Eu(Tp Ph2 )2 ) were designed and synthesized. Their crystal structures, photophysical properties and air stabilities were characterized and discussed. It is found that the introduction of the bulky phenyl group not only increases the air stability by sterically hindering the central Eu 2+ ions, but also tunes the maximum emission wavelength by influencing the ligand field. This work provides rules for regulating the luminescence properties of Eu(ii ) complexes as well as design basis for achieving stable and efficient Eu(ii ) complexes.